Using Junyi Academy to Explore the Difference in Learning Attitude of Remedial Instruction - Shen, Yi -Hsueh; Wu, Chen-Feng; Liu, Li-Hua (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
As the concept of digital learning becomes increasingly clear, so does the labor division of instruction. The teachers who specialize in teaching no longer have to spare efforts to focus on something beyond instruction, which has led to the invention of instruction platforms. This study aims to probe into the difference in learning attitude among the students of the remedial instruction based on Junyi Academy. In this study, Junyi Academy was integrated with the remedial instruction of mathematics. Featuring â€œreplicableâ€, â€œcustomizedâ€ and â€œadaptiveâ€, this platform was employed to provide students with another learning method in the remedial instruction. The quasi-experiment method was adopted; the technology acceptance model (TAM) was taken as the theoretical foundation of the research structure; the behavioral scale which combined Junyi Academy with the remedial instruction of mathematics was used as the research tool; 26 freshmen of a junior college in Miaoli County were taken as the samples. Through the experimental instruction, this study discussed the studentsâ€™ acceptance of the remedial instruction based on Junyi Academy. One of the research purposes is that students will be able to study online by linking their computers with Junyi Academy and will not be confined to the learning time and place designated by schools. Another research purpose is to demonstrate that Junyi Academy is feasible for the remedial instruction.